‘Never let a crisis go to waste’: post-Ebola agenda-setting for health system strengthening in Guinea - Kolie, Delphin (BMJ Glob Health, 2019)
INTRODUCTION: Guinea is a country with a critical deficit and maldistribution of healthcare workers along with a high risk of epidemics' occurrence. However, actors in the health sector have missed opportunities for more than a decade to attract political attention. This article aims to explain why this situation exists and what were the roles of actors in the agenda-setting process of the post-Ebola health system strengthening programme. It also assesses threats and opportunities for this programme's sustainability. METHODS: We used Kingdon’s agenda-setting methodological framework to explain why actors promptly focused on the health sector reform after the Ebola outbreak. We conducted a qualitative explanatory study using a literature review and key informant interviews. RESULTS: We found that, in the problem stream, the Ebola epidemic caused considerable fear among national as well as international actors, a social crisis and an economic system failure. This social crisis was entertained by communities’ suspicion of an 'Ebola-business'. In response to these problems, policy actors identified three sets of solutions: the temporary external funds generated by the Ebola response; the availability of experienced health workers in the Ebola control team; and the overproduction of health graduates in the labour market. We also found that the politics agenda was dominated by two major factors: the global health security agenda and the political and financial interests of national policy actors. Although the opening of the policy window has improved human resources, finance and logistics, and infrastructures pillars of the health system, it, however, disproportionally focuses on epidemic preparedness and response. and neglects patients’ financial affordability of essential health services. CONCLUSION: Domestic policy entrepreneurs must realise that agenda-setting of health issues in the Guinean context strongly depends on the construction of the problem definition and how this is influenced by international actors.